Physician’s perception and practices on antimicrobial resistance in a tertiary care hospital in Bangladesh: a cross-sectional study - Md Fuad Al Fidah; Md Abdullah Saeed Khan; Mohibbul Haque; Mohammad Rezaul Karim; Sabrin Shohid; Pilot Hossain; Rotna Rani Sen; Chaity Dey; Sumaiya Khan; Meherun Nahar Munni; Sonia Afroze Shopna; Razia Shultana; et al. (BMJ Open)
Background Antimicrobial resistance (AMR) is a global health and development concern. Antimicrobial misuse and overuse are key contributors to the emergence of drug-resistant infections.Objective The current study aimed to determine the level of perception and practices of physicians regarding AMR in a tertiary-level hospital.Design Cross-sectional study.Setting A tertiary care hospital in Dhaka, Bangladesh.Participants The study included 360 physicians who worked for more than 6 months in different departments of the hospital.Primary and secondary outcome measures Perceptions of AMR among physicians and secondary outcome measures were to find out the practices of physicians regarding AMR. The current study used 8 defined responses and 6 multiple-choice questions for scoring physicians’ perception of AMR and 12 items to score physicians’ self-reported practice regarding AMR. After converting these scores into percentages, the median split method was used to categorise them into poor and good categories.Results Among 360 physicians, 51% were male, the median (IQR) age was 30 (27.0–34.0) years and 46% had private practices. More than half (52%) had a poor perception of AMR but had good practice (57%) with no significant association between perception and practice. The perception of AMR was significantly associated with age (p=0.048), years in practice (p=0.011) and AMR training (p=0.030). Physicians with private practice had 1.71 times higher odds of having a good perception of AMR (95% CI 2.07 to 2.75, p=0.026) and 2.44 times higher odds of having good practice (95% CI 1.51 to 3.94, p<0.001). The odds of having a good perception of AMR increase 1.20 times with a 1-year increase in years of practice (95% CI 1.01 to 1.44, p=0.042).Conclusion The study revealed that most physicians had poor perception but good practice regarding AMR. Both poor perception and good practice were associated with private practice. To increase good practice and perception regarding AMR, efforts need to be made to establish an AMR education programme for practicing physicians as soon as possible. Moreover, medical audits and continuous quality improvement (such as programmes for antimicrobial stewardship) should be legislated, and monitoring prescribing behaviour and formulating policies accordingly are the way forward in combating AMR.